Cross-border higher education for primary school teachers - Mezgec, Maja (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2019)
The aim of the paper is to discuss the mobility patterns of university students in the context of a border area, taking into consideration the unique characteristics of this region. Special attention is given to the area between Italy and Slovenia where research was conducted among cross-border students attending the study programme for primary school teachers in Slovenia. In the introduction, a distinction is made between cross-border, transnational and overseas education. The following presents the reality of the Italo-Slovene border, an analysis of the factors influencing cross-border mobility and the outcome of the EDUKA2 project.
Keywords: čezmejni študenti; čezmejni visokošolski študij; Italija; manjšine; mednarodni študenti; Slovenija; šolstvo